Coupling surface potential-based adatom-induced nonlocal vibration of a double resonator with an elastic medium under non-uniform thermal intensity - Lamari, Abir; Bourouina, Hicham; Khouni, Soumia; Elaihar , Lamine (Archive of Mechanical Engineering, 2026)
The vibration behavior of an adatom-microresonator featuring a perforated microcore is examined in this paper. The nonlocal strain gradient theory (NSGT) is incorporated to characterize the microscale response. The system is subjected to a nonlinear thermal field and the adsorption of adatoms. The thermal response is modeled by solving a nonlinear steady-state heat conduction equation. Atom-surface interactions are characterized using the Buckingham-Coulomb interatomic potential. Furthermore, the model introduces the coupled dynamic behavior between the two functionally graded porous sandwich (FGPS) microbeams through a defined coupling stiffness term included in the governing equations. To evaluate the impact of rotary inertia, both the Rayleigh beam model (RBM) and the Euler-Bernoulli beam model (EBM) are employed, enabling a comparative analysis. The nonlocal frequencies are calculated using the Navier-type solution method (NTM) and the differential quadrature method (DQM). These frequency results are subsequently visualized through 3D numerical plots. A detailed analysis is performed to investigate the impact of physical parameters such as thermal gradients, porosity distribution, hole number, and adatom density on the nonlocal frequency shift of the system. The findings of this research are significant for advancing the fields of thermal monitoring and gas detection technologies.